Big placenta and anaemia in pregnancy - Begum, Mahamuda; Ara, Shamim; Begum, Shahnaz; Kishwara, Segupta; Rayhan, Khondaker Abu; Hossain, Asad; Nahar, Anjuman (Journal of Shaheed Suhrawardy Medical College, 2012)
Background: Birthing process is the journey of the spirit/ soul. The Placenta is the home for this spirit/ soul for nine months. Placenta has a huge role to play throughout the pregnancy acting as the kidneys, lungs and intestines all in one1. Placenta is an organ that is essential to the survival and growth of the fetus of the mammals. Anaemia in pregnancy is common and one of the risk factors in pregnancy. Maternal anaemia result in fetal hypoxemia and also stimulates placental growth. In anaemia, significant changes both in gross morphology and in histology of the placenta can occur. Type of study: Descriptive. Place of study: Department of Anatomy, Dhaka Medical College, Dhaka. Study period: July 2005 to June 2006. Methods: Sixty (60) placentas of Bangladeshi pregnant women were studied. Out of 60 placentas, anaemic and control group were 40 and 20 respectively. The study was designed to determine, morphological changes of placenta which is influenced by maternal anaemia. Macroscopic dimension of the placenta were measured with observation and dissection method. The samples were divided into group A (control), group B1 (mild anaemia), group B2 (moderate anaemia) and group B3 (severe anaemia). The severe group was not found in present study. Result: In anaemia, placental diameters, surface area and thickness were increased. Conclusion: There were morphological changes of the placenta in association with maternal anaemia. However, comprehensive work considering the physiological, biochemical, genetic as well as further gross, light, electron microscopic and morphometric placental studies are needed in order to support the findings of present study. DOI: http://dx.doi.org/10.3329/jssmc.v1i2.12161 Journal of Shaheed Suhrawardy Medical College Vol.1, No.2, December 2009 p.17-20